War stories - Korman, Gordon (Scholastic Press, 2020)
Twelve-year-old Trevor Firestone loves playing war-based video games and he idolizes his great-grandfather Jacob who came home from World War II a celebrated hero; now ninety-three Jacob wants to retrace his journey in memory and reality and return to the small French village that his unit liberated, and Trevor is going with him--but not everyone in the town want Jacob to come, and Trevor is going to learn an important lesson: real war is not a video game, and valor and heroism can be very murky concepts.